Penerapan Hypnobreastfeeding pada Ibu Menyusui di Posyandu Anyelir Wilayah Kerja Puskesmas Dempo Palembang - Nurul Komariah; Elita Vasra; Kharisma Virgian (IKIP PGRI Bojonegoro, 2022)
ABSTRACTOptimal breastfeeding is very important in health development. It is one of the efforts to improve the nutritional status of the community. Various efforts have been made to educate breastfeeding mothers so that they can provide exclusive breastfeeding. The application of Hypnobreastfeeding has never been done. The goal was to increase the empowerment of breastfeeding mothers through hypnobreastfeeding so that mothers believed that they can give breast milk. The implementation of the activity was followed by breastfeeding mothers who were at the Posyandu Anyelir, the Work Area of the Dempo Palembang Health Center. Hypnobreastfeeding was carried out after conducting interviews with mothers regarding biodata and breastfeeding. Mother felt more relaxed, calm and comfortable. Mothers were confident that they will be able to continue breastfeeding their children. This activity could increase the ability, motivation and higher self-confidence of mothers and can increased the participation of mothers in breastfeeding, especially in exclusive breastfeeding and breastfeeding until the child is 2 years old. To the Puskesmas and Posyandu, it is better to increase counseling and provide breastfeeding motivation for mothers through hypnobreastfeeding. Hypnobreastfeeding can be one of the activities in the class for pregnant women and classes for mothers of toddlers Keywords: Hypnobreastfeeding, Breastfeeding Mother, Breast Milk ABSTRAKPemberian ASI yang optimal sangat penting dalam pembangunan kesehatan. Hal itu merupakan Salah-satu upaya untuk meningkatkan status gizi masyarakat Berbagai upaya dilakukan untuk mengedukasi ibu menyusui agar dapat memberikan ASI Eksklusif. Penerapan Hypnobreastfeeding belum pernah dilakukan. Tujuan yaitu meningkatkan Pemberdayaan ibu menyusui melalui hypnobreastfeeding sehingga ibu yakin bahwa dia bisa memberikan ASI. Pelaksanaan kegiatan diikuti oleh ibu menyusui yang berada di Posyandu Anyelir Wilayah Kerja Puskesmas Dempo Palembang. Hypnobreastfeeding dilakukan setelah melakukan wawancara dengan ibu terkait biodata dan menyusui. Ibu merasa lebih relax, tenang serta nyaman. Ibu yakin akan mampu dan dapat terus menyusui anaknya. Kegiatan ini dapat meningkatkan kemampuan, motivasi serta kepercayaan diri yang lebih tinggi pada ibu serta dapat meningkatkan peran serta ibu dalam menyusui khususnya dalam pemberian ASI Eksklusif dan pemberian ASI sampai anak berusia 2 tahun. Kepada Pihak Puskesmas dan Posyandu lebih meningkatkan penyuluhan dan pemberian motivasi menyusui bagi ibu melalui hypnobreastfeeding. Hypnobreastfeeding dapat menjadi salah-satu kegiatan pada kelas ibu hamil dan kelas ibu balita Kata Kunci: Hypnobreastfeeding, Ibu Menyusu, ASI.